Pengaruh Penggunaan Media Pembelajaran Berbasis Game pada Website Wordwall Terhadap Minat Belajar Ekonomi Siswa Kelas XI SMA Negeri 3 Medan T.A 2024/2025 - Vitaloka.S, Lola; Siar Meiriza, Mica (Universitas Batanghari Jambi, 2025)
This study aims to determine the effect of Wordwall learning media on elementary school students' learning outcomes. This research method uses a quasi-experimental design type Post-test only control group design. The subjects of this study were all 40 students of class XI IPS SMAN 3 Medan. The sampling technique in this study was saturated sampling with a sample size of 20 students as the experimental class and 20 students as the control class. The data collection technique was in the form of a Post-test using multiple-choice test questions. The results showed that the use of wordwall learning media was superior to conventional learning or without involving learning media. Thus, it can be concluded that the use of wordwall learning media has an effect on the learning outcomes of class XI IPS students of SMAN 3 Medan.